2018
DOI: 10.1128/mcb.00409-17
|View full text |Cite
|
Sign up to set email alerts
|

TAB1-Induced Autoactivation of p38α Mitogen-Activated Protein Kinase Is Crucially Dependent on Threonine 185

Abstract: ABSTRACTp38α mitogen-activated protein kinase is essential to cellular homeostasis. Two principal mechanisms to activate p38α exist. The first relies on dedicated dual-specificity kinases such as mitogen-activated protein kinase kinase (MAP2K) 3 (MKK3) or 6 (MKK6), which activate p38α by phosphorylating Thr180 and Tyr182 within the activation segment. The second is by autophosphorylation of Thr180 and Tyr182 in cis, mediated by p38α binding the scaffold protein TAB1. The second mechanism occurs during myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…It has been found that p38 is expressed in both the cytoplasm and the nucleus (but mainly in the cytoplasm), which demonstrates that the distribution of p38 might be critical for regulating substrates. Hence, the potential binding partners of p38 like MK2, MKK3, TAB1 may regulate p38 in different ways such as through phosphorylation sites or subcellular localization [40][41][42]. It is possible RND2 associates with these proteins complex and mediates p38 nucleuscytoplasm transportation directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that p38 is expressed in both the cytoplasm and the nucleus (but mainly in the cytoplasm), which demonstrates that the distribution of p38 might be critical for regulating substrates. Hence, the potential binding partners of p38 like MK2, MKK3, TAB1 may regulate p38 in different ways such as through phosphorylation sites or subcellular localization [40][41][42]. It is possible RND2 associates with these proteins complex and mediates p38 nucleuscytoplasm transportation directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…The protein expression, in vitro activation, and purification procedures followed are described in refs. 22 and 23 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that p38 is expressed in both the cytoplasm and the nucleus (but mainly in the cytoplasm), which demonstrates that the distribution of p38 might be critical for regulating substrates. Hence, the potential binding partners of p38 like MK2, MKK3, TAB1 may regulate p38 in different ways such as through phosphorylation sites or subcellular localization (40)(41)(42). It is possible RND2 associates with these proteins complex and mediates p38 nucleus-cytoplasm transportation directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%